2019
DOI: 10.1002/ar.24277
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role for Endothelial Cell α2β1 Integrin Receptor Clustering in Collagen‐Induced Angiogenesis

Abstract: Angiogenesis is a crucial mechanism of vascular growth and regeneration that requires biosynthesis and cross-linking of collagens in vivo and is induced by collagen in vitro. Here, we use an in vitro model in which apical Type I collagen gels rapidly induce angiogenesis in endothelial monolayers. We extend previous studies demonstrating the importance of the endothelial α2β1 integrin, a key collagen receptor, in angiogenesis by investigating the roles of receptor clustering and conformational activation. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Application of a type I collagen hydrogel to the apical surface of human umbilical vein endothelial cells (HUVECs) induces the reorganization of α2β1 integrins to the apical surface of the cells (Turner et al, 2020). It was further demonstrated that the activation of α2β1 integrins was an important step in rapid tube formation and angiogenesis (Turner et al, 2020).…”
Section: Reproduction and Control Of Cell Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…Application of a type I collagen hydrogel to the apical surface of human umbilical vein endothelial cells (HUVECs) induces the reorganization of α2β1 integrins to the apical surface of the cells (Turner et al, 2020). It was further demonstrated that the activation of α2β1 integrins was an important step in rapid tube formation and angiogenesis (Turner et al, 2020).…”
Section: Reproduction and Control Of Cell Phenotypementioning
confidence: 99%
“…Clustering of apical integrins, particularly activated integrins, appears to be a key component in inducing cell responses ranging from cell migration to increases in permeability (Ojakian and Schwimmer, 1994;Garbi et al, 1996;Zuk and Matlin, 1996;Kam et al, 2013;Walsh et al, 2015;Grassme et al, 2017;Stewart et al, 2017;Badaoui et al, 2020;Mang et al, 2020;Turner et al, 2020). Apical integrin clustering can also drive endocytosis which can be physiological, in the case of integrin turnover during cell migration, but also has the pathological consequences of facilitating infection by bacteria using apical integrins as receptors.…”
Section: Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen eliminated in RPC may be derived from the basement membrane zone [ 6 ]. Angiogenesis is a crucial mechanism of vascular growth and regeneration that requires biosynthesis and cross-linking of collagen in vivo and is induced by collagen in vitro [ 7 ]. The anti-angiogenic, anti-Hedgehog pathway, and anti-inflammatory properties of itraconazole have been widely reported [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The article focused on the fibrillin‐1 expression in aorta and found that it was located to the medial elastic lamellae and that vascular smooth muscle and endothelial cells contribute to the synthesis and deposition (cover, Charbonneau et al, 2020). Vascular endothelial cells also respond to Type I collagen in vitro by clustering alpha2 beta1 integrin receptors as a mechanism of vascular growth and regeneration, and the authors propose that Type I collagen may have applications for promoting vascularization of engineered tissues (Turner et al, 2020). Another unique protein found in endothelial basement membranes is Willebrand factor A‐domain‐related protein (Fitzgerald, 2020).…”
mentioning
confidence: 99%